Zika Virus in the Americas: An Environmental Health Perspective - Bonilla-Soto, Luis A. (Puerto Rico Health Sciences Journal, 2018)
Phylogenetic studies suggest that ZIKV may have been introduced to Brazil, and therefore to the Americas, in 2014 during the World Spring Canoe Championship held in the city of Rio de Janeiro. Since then the virus has spread across Latin America, Caribbean, and North America. It seems clear that Aedes aegypti and, to a lesser extent, Aedes albopictus are the main vectors of the pathogen. ZIKV infection symptoms are similar to other flaviviruses such as a dengue infection and therefore can be easily confounded. Currently, the ZIKV maintains two life cycles. The first, and the original one is the sylvatic/enzootic cycle that occurs in Africa. The second life cycle is the suburban-urban transmission cycle that emerged through natural evolution. ZIKV has gained the ability to maintain this human-endemic cycle in urban and suburban areas. ZIKV has never been isolated from non primates, so it is not clear whether other species can act as reservoir hosts. Several reports have been made of non-vector ZIKV transmission including breast-milk feeding, blood transfusion, sexual intercourse, saliva, urine, and physical contact (sweat, tears). A major global concern with ZIKV infection is the reported increase in cases of microcephaly and Guillain-Barre Syndrome (GBS) in the Americas after the recent ZIKV outbreak. Currently, there is no available vaccine for ZIKV. Therefore, prevention of ZIKV infection must be emphasized by local public health authorities promoting collective responsibility and engagement for integrated vector management through environmental management, biological control, and as a last resource chemical control.